Cover Feature: Paving the Way for Reliable Alzheimer's Disease Blood Diagnosis by Quadruple Electrochemical Immunosensing (ChemElectroChem 9/2022). Issue 9 (30th March 2022) - Valverde, Alejandro; Gordón Pidal, José M.; Montero‐Calle, Ana; Arévalo, Beatriz; Serafín, Verónica; Calero, Miguel; Moreno‐Guzmán, María; López, Miguel Ángel; Escarpa, Alberto; Yáñez‐Sedeño, Paloma; Barderas, Rodrigo; Campuzano, Susana; et al.
Abstract : The Cover Feature illustrates a quadruple immunoplatform for the amperometric determination of blood protein candidate biomarkers (NfL, Tau, p‐Tau and TDP‐43) to assist in the reliable and minimally invasive Alzheimer′s disease diagnosis. The cover was drawn by Beatriz Arévalo and co‐designed with the authors. More information can be found in the Research Article by A. Valverde, J. M. Gordón Pidal et al .